2022
DOI: 10.3389/fsurg.2022.973410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glucose metabolism in breast cancer to guide clinical therapy

Abstract: BackgroundBreast cancer (BRCA) ranks as a leading cause of cancer death in women worldwide. Glucose metabolism is a noticeable characteristic of the occurrence of malignant tumors. In this study, we aimed to construct a novel glycometabolism-related gene (GRG) signature to predict overall survival (OS), immune infiltration and therapeutic response in BRCA patients.Materials and methodsThe mRNA sequencing and corresponding clinical data of BRCA patients were obtained from public cohorts. Lasso regression was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…SDC1 high has varying significance in different kinds of cancer. SDC1 high might predict a poor prognosis of breast cancer, but a better prognosis of colorectal cancer 28 , 29 . To date, few studies have investigated the role of SDC1 in PC 30 .…”
Section: Discussionmentioning
confidence: 98%
“…SDC1 high has varying significance in different kinds of cancer. SDC1 high might predict a poor prognosis of breast cancer, but a better prognosis of colorectal cancer 28 , 29 . To date, few studies have investigated the role of SDC1 in PC 30 .…”
Section: Discussionmentioning
confidence: 98%
“…But the drug sensitivity of IRS2 amplification in breast cancer remains unclear. A recent study established a sugar metabolism-related prognostic model that included IRS2 gene for breast cancer, which could distinguish low-risk patients who were more sensitive to chemotherapy (Mei et al 2022 ). In our study, CUPAx patients with IRS2 mutations showed higher pCR rates (3/4) to neoadjuvant chemotherapy than BCAx patients (0/2) (75% vs. 0%).…”
Section: Discussionmentioning
confidence: 99%
“…Under aerobic conditions, normal cells obtain energy by oxidative phosphorylation (OXPHOS) in the mitochondria. In hypoxia, cells acquire energy via the metabolic pathway of glycolysis rather than mitochondrial processes that consume oxygen[ 54 ]. Despite the availability of sufficient oxygen, malignant tumor cells continue to fulfill their metabolic demands through the glycolytic mode rather than OXPHOS, and this phenomenon is referred to aerobic glycolysis or the Warburg effect[ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%